Decommissioning forecasting and operating cost estimation : Gulf of Mexico well trends, structure inventory and forecast models - Kaiser, Mark J. (Gulf Professional Publishing, 2019)
The US Gulf of Mexico is one of the largest and most prolific offshore hydrocarbon basins in the world with thousands of structures installed in the region and tens of thousands of wells drilled. Over the past decade, a significant number of structures in shallow water have been decommissioned, as operators can no longer "kick the decommissioning can" down the road. This has opened up new markets and additional regulatory oversight with far-reaching implications. This book describes future decommissioning trends and issues and provides guidance for operator budgeting, regulatory oversight, and service sector companies interested in participating in the field. Decommissioning Forecasting and Operating Cost Estimation is the first of its kind textbook to develop models to forecast platform decommissioning in the Gulf of Mexico and to better understand the dynamics of offshore production cost. The book bridges the gap between modeling and technical knowledge to provide insight into the sector. Topics are presented in five parts covering fundamentals, structure inventories and well trends, decommissioning modeling, critical infrastructure issues, and operating cost estimation. Factor models and activity-based cost models in operating cost estimation conclude the discussion. Decommissioning Forecasting and Operating Cost Estimation helps oil and gas professionals navigate through this complex and challenging field providing an invaluable resource for academics, researchers, and professionals. The book will also serve government regulators, energy and environmental engineers, offshore managers, financial analyst, and others interested in this fascinating and dynamic industry